KESETARAAN DAN KELAS SOSIAL DALAM PERSPEKTIF AL-QUR'AN - Barir, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2014)
This study is an effort to find general moral-social in the Qur’an, which focused on the issue of social inequality in social class (patronage, economic class, and race). This research will inspect interweaving between text and context because of comprehensive interpretation not only accepted from text but also must accepted from the context, which appear surrounding the text. From this reason, the double movement will used to analyze every verse of the Qur’an which talking about social class issue with socio-historical approach. More extent, there are three questions will be answered in this research: 1. How did the problem of social class after Qur’anic era? 2. How did the problem of social class in the revelation era? And 3. How does the Qur’anic concept about social class?